Translation of Modal Verbs in Media Texts: Corpus-Based Approach - Ya. A. Volkova; A. S. Korzin; A. D. Uryupina (Научный диалог, 2023)
The main modal verbs of the English language (can, could, may, must, should, need, will, would) in media texts have been studied, namely the ways of their translation into Russian. Using the method of continuous sampling, 50 concordances were selected and analyzed for each of the 8 modal verbs. The material of the study was examples in the field of journalism from the National Corpus of the Russian Language, namely, a parallel subcorpus composed of original texts and their translations. Additionally, a ranking was carried out according to the frequency of modal verbs in the parallel corpus NKRYA (language pair Russian-English) and the English web corpus WebCorp. When comparing, the absolute frequencies of modal verbs were used, since the first corpus is static, and the second is dynamic (replenished daily). The need to supplement the parallel corpus was revealed, since the sorting results were not identical. Based on the analysis of translation transformations, the following was found: literal translation, grammatical substitutions and omission were most often used in the translation of modal verbs in media texts. It has been established that impersonal constructions were often used, and modality was transmitted using linguistic means of another level.